Determinan kedalaman kemiskinan di Kalimantan Barat: Peran pertumbuhan ekonomi dan partisipasi angkatan kerja perempuan - Fathia Mirda Ramadhani; Eko Supriyanto (Journal of Economics Research and Policy Studies, 2025)
This study examines the effects of economic growth and women’s labor force participation on the poverty depth index across districts/cities in West Kalimantan from 2018 to 2023. Using a descriptive quantitative approach, the study draws on secondary data from Indonesia’s Central Statistics Agency (BPS) and applies panel data regression. The findings indicate that economic growth is positively associated with poverty depth, suggesting that poor households have not fully shared in growth in West Kalimantan’s districts/cities and that poverty depth has therefore not been reduced. Meanwhile, women’s labor force participation shows a negative but insignificant relationship with poverty depth, implying that greater female participation tends to reduce poverty depth. However, the effect is not strong enough to be confirmed. Overall, the results highlight the need for more inclusive economic development policies, along with improved job quality and access for women, to help reduce poverty depth in West Kalimantan.